USE OF PERSONAL PROTECTIVE EQUIPMENT IN A HOME CARE SERVICE - Jéssica Fernanda Corrêa Cordeiro; Amanda Pavinski Alves; Elucir Gir; Diego Oliveira Miranda; Silvia Rita Marin da Silva Canini (Universidade Federal do Paraná, 2016)
A cross-sectional study was conducted at a home care service in the state of São Paulo. The objective of the study was to identify the use of personal protective equipment, safety devices, the disposal of sharp objects, and other factors that make difficult and/or facilitate such use by professionals of the nursing team. The population was made up of 45 participants who reported using personal protective equipment. They all reported using gloves, frequent procedures that required their use were dressings and administration of medications. Although it was reported that the participants did not have difficulty in using personal protective equipment, and that they were concerned about their own safety, full adherence was lacking. Therefore, further studies that are able to evaluate how home care services really occur are necessary, so that prevention strategies can be identified and incorporated into professionals' practice.